ANTAGONISTIC ACTIVITY OF ENDOPHYTIC FUNGI ISOLATED FROM ALOE VERA LEAVES AGAINST SOME PLANT PATHOGENIC FUNGI - M. A. A. Al Nuaimy; S. N. Hawar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The present study was aimed to test the antagonistic activity of endophytic fungi isolated from Aloe vera leaves against a number of plant-pathogenic fungi. The results showed that the highest antagonistic activity was exerted by Penicillium chermesinum against the pathogenic fungus Rhizoctonia solani, with an inhibition rate of 78.57%. Also, Talaromyces verruculosus and P. chermesinum showed their highest antagonistic activities against pathogenic fungus Fusarium 1 with inhibition rates of 61.79% and 61.53%, respectively, while T. verruculosus showed an inhibition rate of 62.91% against the pathogenic fungus Fusarium 2. Most of the endophytic fungi showed the least percentage of inhibition against Macrophomina phaseolina compared to the rest of the pathogenic fungi. The fungal filtrates showed a concentration-dependent inhibition rate against the plant pathogens, with a range of 0.00-48.13%. The highest inhibitory activity of Aspergillus niger was recorded at a concentration of 60% against Fusarium 2, R. solani, and Fusarium 1, with rates of 48.13, 37.39, and 36.66%, respectively. The results also showed the ineffectiveness of all fungal filtrates against the pathogenic fungus M. phaseolina. Chemical analysis of the filtrates of the endophytic fungi which showed antagonistic activity against pathogenic fungi was also conducted by using GC-MS. The results showed the presence of effective compounds with biological effects, such as Pentadecanoic acid, Oleic Acid, Limonene, cis-Vaccenic acid, Hexanedioic acid, bis(2-ethylhexyl) ester, Cycloheptasiloxane, and tetracamethyl-.